Highly Selective Voltammetric Sensor Based on Molecularly Imprinted Polymer and Carbon Nanotubes to Determine the Dicloran Pesticide in Biological and Environmental Samples. (2017) - Shahtaheri, Seyed Jamaleddin; Faridbod, Farnoush; Khadem, Monireh
Extended Abstract: Introduction: Despite of increasing the food production by application of pesticides, the wide use of them can lead to environmental pollution and their residues in food. Due to the increasing application of pesticides, reliable and accurate analytical methods are necessary to analyze different occupational and environmental samples like air, water, soil, as well as also food containing these compounds. There are some traditional techniques to determine the pesticides such as liquid chromatography and gas chromatography with electron capture detection. The mentioned techniques are very expensive and a well-equipped laboratory and well-trained analysis operators are required. A sample pre-treatment step is needed to determine the analytes at ppb levels. Therefore, in the last few years many sensitive, selective, and accurate methods have been developed to determine the trace toxic species like pesticides. Electrochemical sensors are the appropriate and interested devices to monitor the trace and even ultra-trace pesticides. Molecular imprinted polymers (MIPs) can be used as recognition elements or modifying agents in sensors structure to increase their selectivity and improve their response. Recently, modified electrode by different modifying agents like MIPs and various nano structures are being used for quantification of analytes because of their interesting advantages. Modified electrodes may be used in combination with different electrochemical techniques. The aim of this study was to synthesize a molecularly imprinted polymer for dicloran for first time and then to apply it as a recognition element in the nano-composite carbon paste electrode for selective and sensitive electrochemical determining the dicloran pesticide in environmental and biological samples. Methods: Multi-walls carbon nanotubes (MWCNTs) and a molecularly imprinted polymer (MIP) were used as the modifiers in senor composition. A dicloran selective MIP and a non-imprinted polymer (NIP) were synthesized and applied in the carbon paste electrode. To prepare the bare carbon paste electrode (CP), graphite, MWCNT and paraffin oil were mixed. The MIP-CP and NIP-CP were prepared by mixing different percentages of graphite, MWCNT, paraffin oil, and MIP or NIP. This mixture was homogenized and final paste was packed into the end of an electrode body. After the optimization of electrode composition, it was used to extract the analyte in the sample and then was inserted in the electrochemical cell to determine the concentration of extracted analyte. Some parameters affecting the sensor response were optimized in the extraction and analysis steps, such as sample pH, electrolyte concentration and pH, stirring rate of analyte solution, as well as the instrumental parameters of square wave voltammetry (square wave amplitude and frequency, deposition potential and its exertion time, and electrolyte concentration). Results and Discussion: The MIP-CP electrode showed very high recognition ability in comparison to NIP-CP. The CP containing 22% MIP and 3% MWCNTs had the highest efficiency to adsorb the analyte and it was selected for later experiments. The electrode with MIP was very selective for dicloran, so that, other pesticides indicated no significant impact on its responses. Findings demonstrated the ability of MIP-CP electrode to interact strongly with the target compound due to specific cavities for molecules of interest in the MIP structure. The optimum conditions to extract the analyte on the electrode surface included the extraction pH of 6, the solution stirring rate of 700 rpm, and the extraction time of 20 min. In addition, the optimum analysis conditions were obtained as follow: the square wave amplitude 0.15 V, frequency 150 Hz, deposition potential of -0.5 V, its exertion time of 15s, analysis pH of 8, and electrolyte (KCl) concentration of 0.04 mol L -1 . After optimization of all effective parameters on electrochemical determination of dicloran, the difference between responses of prepared MIP and NIP was studied. There was significant difference (P< 0.05) between these polymers to adsorb dicloran molecules, proving the formation of selective adsorption sites in the MIP structure. Figure 1 indicates the square wave voltammograms related to determination of defined concentration of dicloran by MIP-CP, NIP-CP, and bare CP. Finally in method validation, the obtained linear range in calibration curve was 1×10 -6 to 1×10 -9 molL -1 (R 2 : 0.987), The limit of detection (LOD) and limit of quantification (LOQ) were 4.8×10 -10 and 9.4×10 -10 mol L -1, respectively. Conclusion: In this work, a high selective square wave voltammetric sensor for the rapid detection of trace amounts of dicloran in environmental and biological samples has been designed and applied. The modification of electrode can considerably enhance the selective response of electrode to determine the analyte of interest. The designed sensor was successfully used for determination of dicloran in different real samples (tap water, river water, and urine) with no special sample preparation procedure. The ability of MIP-CP electrode to interact strongly with the target compound due to specific cavities lead to high selectivity.